Impact of the Number of Cores on the Prostate Cancer Detection Rate in Men Undergoing in-Bore Magnetic Resonance Imaging–Guided Targeted Biopsies. Issue 2 (March 2021) - Subramanian, Naveen; Recchimuzzi, Debora Z.; Xi, Yin; Diaz de Leon, Alberto; Chen, Heng; Xie, Donglu; Goldberg, Kenneth; Rofsky, Neil M.; Pedrosa, Ivan; Costa, Daniel N.
Abstract : Objective: To determine the incremental detection rate of clinically significant prostate cancer (csPCa) provided by sequential cores during in-bore magnetic resonance imaging (MRI)-guided prostate biopsies. Methods: Single-center, retrospective interpretation of prospectively acquired data in men without previous diagnosis of csPCa who underwent in-bore MRI-guided prostate biopsy between May 2017 and December 2019. Endpoints included detection of csPCa (grade group [GG] ≥ 2) and rate of GG upgrade provided by additional cores. Descriptive statistics presented as mean and standard deviation for the continuous variables, and frequency and percentage for the categorical variables. Results: Four hundred and forty-three men with 747 lesions met eligibility criteria. Clinically significant prostate cancer was detected in 43.1% (322/747) of the biopsied lesions and GG 2 PCa or greater was identified by the first core in 78.3% (252/322) of them. On a per-core basis, cores 2, 3, 4, and 5 found new csPCa in 6% (42/744), 4% (26/719), 1% (2/137), and 0% (0/11) of the cases. Core biopsy 2, 3, 4, and 5 resulted in GG upgrade in 12% (91/744), 7% (49/719), 7% (9/137), and 0% (0/11) of the lesions, respectively. Each additional core was associated with a mean increase of 5 minutes in the duration of the biopsy. Conclusions: In men undergoing in-bore MRI-guided prostate biopsies, 3 targeted cores per lesion provide an optimal trade-off between detection of clinically significant tumors and biopsy duration.